2018
DOI: 10.1080/01635581.2018.1446090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Green Tea Polyphenol Epigallocatechin-3-Gallate on Glioma: A Critical Evaluation of the Literature

Abstract: The review discusses the effects of Epigallocatechin-3-gallate Gallate (EGCG) on glioma as a basis for future research on clinical application of EGCG. Epidemiological studies on the effects of green tea or EGCG on the risk of glioma is inconclusive due to the limited number of studies, the inclusion of all tea types in these studies, and the focus on caffeine rather than EGCG. In vivo experiments using EGCG monotherapy are inconclusive. Nevertheless, EGCG induces cell death, prevents cellular proliferation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 113 publications
(241 reference statements)
0
19
0
Order By: Relevance
“…The uPA antisense resulted in a loss of invasive capacity and a reduction of active forms of PI3K and Akt (Gondi, Lakka et al 2004, Hatoum, Mohammed et al 2019. The serine protease uPA can active MMPs and increase degradation of the extracellular matrix, but EGCG inhibits uPA and prevents invasion in U87 glioblastoma cell line (Le, Leenders et al 2018). Besides, the nuclear translocation of p65 subunit of NF-κB is inhibited by Resveratrol , therefore, Resveratrol can suppress NF-κB factor activation which cause to a downregulation of the expression of uPA/uPAR genes and reduces invasion of glioma cells (Andrade, Ramalho et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The uPA antisense resulted in a loss of invasive capacity and a reduction of active forms of PI3K and Akt (Gondi, Lakka et al 2004, Hatoum, Mohammed et al 2019. The serine protease uPA can active MMPs and increase degradation of the extracellular matrix, but EGCG inhibits uPA and prevents invasion in U87 glioblastoma cell line (Le, Leenders et al 2018). Besides, the nuclear translocation of p65 subunit of NF-κB is inhibited by Resveratrol , therefore, Resveratrol can suppress NF-κB factor activation which cause to a downregulation of the expression of uPA/uPAR genes and reduces invasion of glioma cells (Andrade, Ramalho et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EGCG is implicated in down-regulating Wnt signaling in breast cancer cells and up-regulating p53 transcription in LNCaP prostate cancer cells [5]. EGCG inhibits the protein expressions of telomerase, and also down-regulates certain inflammatory signaling cascades, such as NFkB, platelet-derived growth factor receptor (PDGF), and IGF-1R in glioma cells [91].…”
Section: Epigallocatechin Gallatementioning
confidence: 99%
“…A recent study described anti-glioblastoma effects of EGCG on U87 MG glioblastoma cell line enriched with Glioma Stem-Like Cells (GSLCs); EGCG treatment profoundly reduced the neurosphere formation and migration of tumor cells [126]. Moreover, EGCG down-regulates P-glycoprotein in vitro that results in the sensitization of glioma stem cells to temozolomide [91,127]. EGCG significantly down-regulated Bcl-2 expression and Akt phosphorylation, and increased Bax expression and PARP cleavage, thereby inducing apoptosis in GSLCs [126].…”
Section: Epigallocatechin Gallatementioning
confidence: 99%
“…In the last decade, bioactive phytochemicals have been regarded as mostly non-toxic compounds for the treatment of many forms of cancers, including brain tumors and gliomas [17]. Several authors reported inhibition of cell proliferation of glioma by compounds such as Curcumin (Cur), isothiocyanate derivatives, resveratrol, and catechins, such as Epigallocatechin-3-Gallate (EGCG) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%